Review of Indian Gentian (Gentiana kurroo Royle) - A Medicinal Plant of High Conservation Concern - Kumar, Vishavjit (Indian Forester, 2024)
Indian Gentian (Gentiana kurroo Royle) a member of family Gentianaceae is endemic to the north and north-western parts of the Indian Himalayan region, being 80 per cent of its populations confined to this region only, and rest in Pakistan and Nepal. Excessive harvesting of roots and rhizomes from its remnant natural habitats for medicinal uses has threatened the species to extinction and listed in the 'Critically Endangered' category of the IUCN Red List of Threatened Plants. Gentiopicroside, a secoiridoid glycoside, is the major biologically active constituent both in roots and rhizomes as well in leaves. The species once thought to be extinct from Kashmir and Uttarakhand Himalayas has been rediscovered from both the regions after more than six and five decades respectively of its last reporting. The available knowledge on its ecology, species survival strategy, and phytochemical and pharmacological profile has been reviewed in this article.